Seychelles : 2017 Article IV Consultation and Sixth Review Under the Extended Arrangement-Press Release; Staff Report; and Statement by the Executive Director for Seychelles. - International Monetary Fund. African Dept. (Washington, D.C. : International Monetary Fund, 2017)
This 2017 Article IV Consultation highlights Seychelles' continued strong macroeconomic performance in 2016. Economic growth reached 4.5 percent, reflecting increased tourist arrivals, stronger output in the fishing industry, and expanding credit to the private sector. Helped by low commodity prices and a stable exchange rate, inflation (year over year) was negative throughout early 2017. The external current account deficit remained largely unchanged, while gross international reserves at the end of 2016 reached four months of prospective imports of goods and services. With continued foreign investment and rising arrivals in the tourism sector, the growth outlook for 2017 remains positive.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet